Rancang Bangun Sistem Sortir Buah Apel Menggunakan Sensor Warna Dan Sensor Suhu - Mohammad Fauzin Amin; Sabriansyah Rizqika Akbar; Edita Rosana Widasari (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2017)
The development of science and technology makes the quality of human life is growing, the processing industry and agricultural estates are also growing rapidly. One of the stages in the processing of agricultural products and plantations is the selection of products based on quality, such as fruit maturity level. The process of selecting agricultural products and plantations is highly dependent on the human perception of the fruit color composition factor. Apple is one type of fruit that is very popular and is often consumed by the community, both from the young to the old. Apples also contain vitamins needed by the human body, including vitamins A, B1, and C. So, it can be said that apples are a very popular fruit because the benefits are very abundant. But apple lovers are often confused in terms of choosing apples that have ripe maturity. Sometimes apple entrepreneurs still use the manual way to distinguish the maturity of apples, while the way that is done by the tenega man is often inaccurate and different in its determination. The difference is due to differences in perceptions on everyone. Therefore built a tool that can make the selection of apples based on quality, especially color automatically. So that will be able to produce a more accurate grouping of apples, which further simplify the packaging process and also save time, effort and cost. Design This tool uses RGD LDR and DHT11 as sensors to read the maturity of apples. RTC 1307 is used as a timer to send data from sensor, arduino nano as microcontroller and NRF24L01 as a data transmission device between two transmitter nodes and receiving node.